Developing mRNA Nanomedicines with Advanced Targeting Functions - Wang, Ji; Cai, Lijun; Li, Ning; Luo, Zhiqiang; Ren, Haozhen; Zhang, Bing; Zhao, Yuanjin (Nano-Micro Letters, 2025)
The emerging messenger RNA (mRNA) nanomedicines have sprung up for disease treatment. Developing targeted mRNA nanomedicines has become a thrilling research hotspot in recent years, as they can be precisely delivered to specific organs or tissues to enhance efficiency and avoid side effects. Herein, we give a comprehensive review on the latest research progress of mRNA nanomedicines with targeting functions. mRNA and its carriers are first described in detail. Then, mechanisms of passive targeting, endogenous targeting, and active targeting are outlined, with a focus on various biological barriers that mRNA may encounter during in vivo delivery. Next, emphasis is placed on summarizing mRNA-based organ-targeting strategies. Lastly, the advantages and challenges of mRNA nanomedicines in clinical translation are mentioned. This review is expected to inspire researchers in this field and drive further development of mRNA targeting technology. Highlights: 1 The structure and modification strategies of messenger RNA (mRNA), along with advanced delivery carriers, are thoroughly reviewed to showcase their role in targeted drug delivery. 2 Recent advancements in mRNA nanomedicines, focusing on targeted strategies for various organs, are summarized to illustrate their therapeutic potential. 3 The major challenges and future perspectives for the clinical translation of targeted mRNA nanomedicines are discussed, emphasizing solutions to biological barriers.